The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/chem.201404759
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Relationship of Supramolecular Ferroelectric [H‐66dmbp][Hca] Accompanied by High Polarization, Competing Structural Phases, and Polymorphs

Abstract: Three polymorphic forms of 6,6'-dimethyl-2,2'-bipyridinium chloranilate crystals were characterized to understand the origin of polarization properties and the thermal stability of ferroelectricity. According to the temperature-dependent permittivity, differential scanning calorimetry, and X-ray diffraction, structural phase transitions were found in all polymorphs. Notably, the ferroelectric α-form crystal, which has the longest hydrogen bond (2.95 Å) among the organic acid/base-type supramolecular ferroelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…The presence of two more nitrogen atoms in each molecule of the base permits the acid and base molecules to self-assemble alternately to form linear supramolecular chains. [28][29][30] The resulting series of acid-base cocrystals provide a suitable platform for achieving a deeper understanding of how hydrogen-bonded structures show changes in their microscopic ferroelectric properties and related macroscopic properties through the ordering or dynamics of protons. Earlier studies on some ionic crystals found some analogous behaviors with the KDP family; deuterium substitution elongated their hydrogen-bond length, and increased the potential-energy barriers for proton dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of two more nitrogen atoms in each molecule of the base permits the acid and base molecules to self-assemble alternately to form linear supramolecular chains. [28][29][30] The resulting series of acid-base cocrystals provide a suitable platform for achieving a deeper understanding of how hydrogen-bonded structures show changes in their microscopic ferroelectric properties and related macroscopic properties through the ordering or dynamics of protons. Earlier studies on some ionic crystals found some analogous behaviors with the KDP family; deuterium substitution elongated their hydrogen-bond length, and increased the potential-energy barriers for proton dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Thus, the T c difference between D-ST and D-TTF cannotb ee xplained by the differences in d OO ,i nc ontrast to the case of conventional order-disorder-type H-bonded( anti)ferroelectrics. [25] Therefore, one can imagine that significant changes in the p-p interactions and electronic structure, which originate from S/Se substitution, influence not only physicalp roperties such as 1, E a ,a nd 2 J/k B ,b ut also the phasetransition temperature T c .Asmentionedabove, this phase transition is fundamentally based on the interplay between Hbond dynamics and p electrons. Thus, if such significant changes in the p-electronic structure occur,t he interplaya nd resultingp hase-transition nature should also be modulated; thus resulting in the differencei nT c ( % 10 K) between D-ST and D-TTF,a lthough d OO in D-ST is slightly shorter than that in D-TTF.T his scenario means that, in this system, the H-bondd ynamics or phase-transition naturec an be varied by the modulation of not only the H-bond itself (e.g.,H /D substitution), but also its adjacent TTF molecular p-electron system (e.g.,S /Se substitution), which raises the possibility of the realization of variousk inds of phase-transition nature and switchingf unction by chemical modification and functionalization of this new type of switchable molecular crystals.…”
Section: X-ray Crystal-structure Analysismentioning
confidence: 99%
“…The proton-transfer-type organic ferroelectrics are a novel class of ferroelectric materials composed of π-conjugated molecules that are linked by hydrogen bonding [8][9][10]. The lattice elastic energy in these materials is negligible because spontaneous polarization originates from the cooperative transfer of protons within the crystals as well as from the electric dipoles of π-conjugated organic molecules [11,12]. Tactical design of the molecular materials with use of hydrogen bonding allows to reverse the crystal symmetry with cooperative proton transfer and least change in the structures of host molecular moieties.…”
Section: Introductionmentioning
confidence: 99%